Orthodontic Conundrums Part 1: Transposition – an Update on Presentation and Treatment Modalities. (2nd October 2020) - Adam, Naeem I; Jowett, Adam; Hodge, Trevor
Abstract : This is the first article in a three-part series considering uncommon dental anomalies and treatment approaches. Dental transpositions are rare anomalies which may present to the general dental practitioner or orthodontist. The management of transpositions is dependent on several factors, including the sub-type, severity and the other salient features of the malocclusion. Transposition may either be accepted or orthodontically corrected and the adoption of either approach must be preceded by thorough assessment of the patient. CPD/Clinical Relevance: The presentation and management of transposition is variable. The general dental practitioner must be aware of the clinical features of a developing transposition as certain treatment options are only possible before the transposition is fully established. In addition, the orthodontist must be mindful of the potential for iatrogenic harm if these dental anomalies are managed injudiciously.